Extraction of arabinoxylans from wheat bran using hydrothermal processes assisted by heterogeneous catalysts. (15th March 2017) - Sánchez-Bastardo, Nuria; Romero, Alberto; Alonso, Esther
Highlights: Heterogeneous catalysts intensify hydrothermal fractionation. Effects of ruthenium catalyst, temperature, time and catalyst support are discussed. RuCl3 -based catalysts show good activity for the arabinoxylans extraction. Liquid extracts are characterized in terms of sugars, molecular weight and purity. Abstract: The extraction/hydrolysis process of arabinoxylans from destarched wheat bran was studied in this work using different mesoporous silica supports and the corresponding RuCl3 -based catalysts. The effects of temperature, time, catalyst supports and ruthenium catalysts were investigated and discussed in terms of the arabinoxylans extraction yield and their polymerization degree. Relatively high temperatures (180 °C), short extraction times (10 min) and RuCl3 supported on Al-MCM-48 led to a high amount of extracted arabinoxylans (78%) with a low molecular weight (9 kDa). Finally, a relation between the operating conditions, the arabinoxylans extraction yield and the molecular weight was stablished based on the obtained results.